QUANTITATIVE GENETIC PARAMETERS FOR GROWTH-RELATED AND MUSCLE FIBER TRAITS OF MACROBRACHIUM ROSERNERBII IN INDIA - Shetty, Chethan P.; Jahageerdar, Shrinivas; Venugopal, G. (Journal of Indian Fisheries Association, 2011)
Freshwater prawn Macrobrachium rosenbergii is an important commercial food source in India. In order to augment production, selective breeding programs primarily target two traits: growth rate and body weight, which mainly depend on the weight of the skeletal muscle tissue. The study, focused on the smallest functional unit of the skeletal muscle tissue, the fasciculus, and estimated the heritabilities of total length, body weight, number and diameter of muscle fascicule and genetic correlations between them at 60 and 180 days hapa-age. The heritability estimates for total length and body weight at 60 days hapa-age was 0.20 ± 0.01 and 0.006 ± 0.003, respectively. Heritability estimate for muscle fasciculi diameter at 60 days hapa-age was 0.074 ± 0.01 and the muscle fasciculi numbers was 0.87 ± 0.01. The genetic correlations between total length and body weight at different hapa-age were consistently high. All the estimates of heritability and genetic correlation in full-sib families of M. rosenbergii indicate a significant genetic component to early growth. The studies suggest that muscle fascicule characteristics are strong candidates for heritable traits and may be incorporated as selection objectives in breeding programs of M. rosenbergii. Key words: Macrobrachium rosenbergii, Body weight, Heritability, Genetic correlation, Muscle growth.